Investigation of The Presence of Aedes aegypti Larvae and Its Related Factors in Air Putih Community Health Center, Samarinda - Sri evi Newyearsi; Silviana Silviana (Insights in Public Health Journal, 2022)
Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia until now because there are still many morbidity and mortality rates every year. DHF cases in the working area of the Air Putih Health Center fluctuate every year, in 2019 there were 109 cases, in 2020 there were 29 cases and in 2021 there were 44 cases. The purpose of this study was to determine the relationship between breeding places and PSN behavior with the presence of Aedes aegypti mosquito larvae in the working area of the Air Putih Public Health Center, Samarinda City. This study used quantitative, analytic survey methods with a cross-sectional approach where the subjects in this study were houses within the working area of the Air Putih Community Health Center with a sample of 59 houses, a sampling technique set by WHO. Collecting data with a questionnaire, check list and analyzed using the fisher's exact test. As for the bivariate test results, it was found that there was a relationship between TPA for daily needs (p-value = 0.00), TPA not for daily needs (p-value = 0.00) and PSN behavior (p-value = 0.05 ) with the presence of Aedes aegypti mosquito larvae in the working area of the Air Putih Public Health Center, Samarinda City. Suggestions in this study, the people in the working area of the Air Putih Health Center can reduce mosquito breeding places, drain the TPA regularly and bury used items that are not used. It is also hoped that the Puskesmas can improve coordination with the community and cadres in checking mosquito larvae regularly so that they can eradicate the DHF vector.